Design and Modeling of a Single and Matrix Printed Band Antenna Using HFSS Software - عراج, سهى (Latakia University Journal -Engineering Sciences Series, 2024)
The research includes an introduction to the antennas and parameters of the study of each antenna in general, and definition of the types of antennas according to a simplified explanation before reaching the study of the printed slat antennas, their types methods of manufacturing and feeding them in the method of the transmission line model. then we continue to present the array antennas of which the second part of research is the practical section which includes a practical design study of a single segmental antenna using the HFSS simulation program and an array design of these antennas. the biggest problem facing this research is the difficulty of practical implementation of the required antennas, as a result of the unavailability of the required insulting materials to form the base layer, and the lack of laboratories necessary to measure, and test these antennas if they are designed. Therefore, we resorted to a design similar to the patch antennas found in the antenna laboratory at the university and compared the results obtained in the simulation with the practical results.